Components of Herbal Plants that Inhibit HIV in Public Health Welfare Efforts: Literature Review - Safitri, Sella Dwi; Sofiyah, Shohebatuz (Journal of Advances in Medicine and Pharmaceutical Sciences, 2022)
The highest number of HIV/AIDS sufferers is of childbearing age. Stigma, discrimination, and lack of knowledge about HIV and AIDS are the biggest problems in Indonesia in an effort to reduce the prevalence of PLWHA. Most people still do not know about the causes and modes of transmission of HIV/AIDS. Predisposition is a factor that causes a mother or baby with HIV/AIDS to have a great chance of contributing to maternal and infant mortality, which greatly determines the health status of a country's population. The number of people living with HIV is increasing in 50 countries, including Indonesia, with more than 1.8 million people newly infected with this deadly virus in 2017. Around 180,000 children (0-14 years) are infected with the HIV virus and 110,000 children die from related diseases with AIDS. The purpose of this study is to provide services that can improve health, especially for mothers and children infected with the HIV virus and improve the welfare of the community from HIV/Aids disease by being able to accept their condition, be sincere, and be able to maintain relationships with the community. By using the literature review method collected through national and international journals and research articles. The result of this literature review is to obtain the latest innovations in HIV/AIDS prevention by giving herbal medicines that can play an active role in suppressing the levels of the HIV virus in the prevention of HIV/AIDS in pregnant women and their babies, through the health services provided by medical personnel and government infrastructure, is expected to reduce the rate of HIV transmission to the mother and fetus.